Monitoring and Managing BTK Inhibitor Treatment-Related Adverse Events in Clinical Practice - Susan M. O’Brien (Frontiers Media S.A., 2021)
Bruton tyrosine kinase (BTK) inhibitors represent an important therapeutic advancement for B cell malignancies. Ibrutinib, the first-in-class BTK inhibitor, is approved by the US FDA to treat patients with chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL), and mantle cell lymphoma (MCL; after ≥1 prior therapy); and by the European Medicines Agency (EMA) for adult patients with relapsed/refractory (R/R) MCL and patients with CLL. Ibrutinib treatment can be limited by adverse events (AEs) including atrial fibrillation, arthralgias, rash, diarrhea, and bleeding events, leading to drug discontinuation in 4%–26% of patients. Acalabrutinib, a second-generation BTK inhibitor, is approved by the FDA to treat adult patients with CLL/SLL or MCL (relapsed after 1 prior therapy); and by the EMA to treat adult patients with CLL or R/R MCL. The most common AE associated with acalabrutinib is headache of limited duration, which occurs in 22%–51% of patients, and is mainly grade 1–2 in severity, with only 1% of patients experiencing grade ≥3 headache. Furthermore, acalabrutinib is associated with a low incidence of atrial fibrillation. Zanubrutinib, a selective next-generation covalent BTK inhibitor, is approved by the FDA to treat adult patients with MCL who have received ≥1 prior therapy, and is under investigation for the treatment of patients with CLL. In the phase 3 SEQUOIA trial in patients with CLL, the most common grade ≥3 AEs were neutropenia/neutrophil count decreased and infections. This review provides an overview of BTK inhibitor-related AEs in patients with CLL, and strategies for their management.